![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx%2B3+%5Cneq+0%7D+%5Catop+%7B4x%5E2-16%3E%3D0%7D%7D+%5Cright.+%5Cleft+%5C%7B+%7B%7Bx+%5Cneq+-3%7D+%5Catop+%7B4x%5E2%3E%3D16%7D%7D+%5Cright.+%5Cleft+%5C%7B+%7B%7Bx+%5Cneq+-3%7D+%5Catop+%7Bx%5E2%3E%3D4%7D%7D+%5Cright.+%5Cleft+%5C%7B+%7B%7Bx+%5Cneq+-3%7D+%5Catop+%7B%7Cx%7C%3E%3D2%7D%7D+%5Cright.+%5Cleft+%5C%7B+%7B%7Bx+%5Cneq+-3%7D+%5Catop+%7Bx%3E%3D2%7D%7D+%5Catop+%7B%7D%7Dx%3C%3D-2+)
=0}} \right. \left \{ {{x \neq -3} \atop {4x^2>=16}} \right. \left \{ {{x \neq -3} \atop {x^2>=4}} \right. \left \{ {{x \neq -3} \atop {|x|>=2}} \right. \left \{ {{x \neq -3} \atop {x>=2}} \atop {}}x<=-2 " alt=" \left \{ {{x+3 \neq 0} \atop {4x^2-16>=0}} \right. \left \{ {{x \neq -3} \atop {4x^2>=16}} \right. \left \{ {{x \neq -3} \atop {x^2>=4}} \right. \left \{ {{x \neq -3} \atop {|x|>=2}} \right. \left \{ {{x \neq -3} \atop {x>=2}} \atop {}}x<=-2 " align="absmiddle" class="latex-formula">
Общий ответ: (-∞;-3)∪(-3;-2]∪[2;+∞)